Tripled coincidence point theorems with M-invariant set for a α-ψ-contractive mapping in partially metric spaces - Phakdi Charoensawan (2018)
© 2018 by the Mathematical Association of Thailand. All rights reserved. In this paper, we introduce the notion M-invariant set for mapping α: X3× X3→ [0, +∞). We show the existence of a tripled coincidence point theorem for a α-ψ-contractive mapping in partially ordered complete metric spaces without the mixed g-monotone property, using the concept of M-invariant set. We also show the uniqueness of a tripled common fixed point for such mappings and give some examples to show the validity of our result.